GUT MICROBIOTA AND DEPRESSION: MECHANISMS, EVIDENCE, AND IMPLICATIONS FOR TREATMENT AND SPORT: A CURRENT REVIEW - Bartosz Wiśniewski; Dominika Pachnowska; Kacper Cholewiński; Natalia Badowska; Izabela Matuszek; Natalia Pluta; Katarzyna Aleksandra Nowak; Alicja Rutkowska-Nowosielska; Oliwia Nikola Czekanow; Jerzy Demkow; Zofia Kania-Bonicka (International Journal of Innovative Technologies in Social Science, 2026)
Background: Major depressive disorder (MDD) affects over 264 million people globally. Growing evidence implicates the Microbiota-Gut-Brain axis in its pathogenesis, yet mechanisms and therapeutic implications remain incompletely understood. Aim: To synthesise evidence on gut microbiota alterations in MDD, neurobiological mechanisms, microbiota-targeted interventions, and implications for sport populations. Material and methods: A narrative review of 28 peer-reviewed publications (2019-2025) using PubMed. Search terms included gut microbiota, major depressive disorder, dysbiosis, probiotics, HPA axis, and short-chain fatty acids. Results: Depletion of SCFA-producing genera – particularly Faecalibacterium, Coprococcus, and Prevotellaceae – alongside enrichment of pro-inflammatory taxa was identified across multiple systematic reviews. Three neurobiological pathways were delineated: serotonergic and GABAergic dysregulation, HPA axis dysfunction via the kynurenine pathway, and LPS-mediated neuroinflammation. Adjunctive probiotic supplementation demonstrated a modest antidepressant effect (SMD = 0.83). Moderate physical activity increases SCFA-producing taxa overlapping with those depleted in MDD. Conclusions: Gut microbiota alterations are associated with MDD through identifiable pathways. Probiotics show adjunctive therapeutic potential. Sport populations represent a clinically relevant group for microbiota-targeted research.